A 2-Stage Root Analog Implant with Compact Structure, Uniform Roughness, and High Accuracy. (June 2023) - Yu, X.; Feng, B.; Lan, Y.; Li, J.; Ye, G.; Li, Q.; Zhao, F.; Gu, Y.; You, D.; Zhu, Y.; Yu, M.; Wang, H.; et al.
Immediate implant placement has the advantages of shortening the operation time, reducing the treatment cycle and cost. At present, this technology has been used widely, but the indications of immediate implantation are still limited. Here, a novel type of root analog implant (RAI) was manufactured by selective laser melting technology to address the limitation. Under optimized condition, RAIs were printed with the internal density of 99.73% and the uniform surface roughness of 11 μm (Sa). Besides, the deviation between RAI specimen and design models is controlled within 0.15 mm after optimizing scanning parameters. The substrate printed could promote human bone marrow stromal cell proliferation, spreading, and osteogenic differentiation. The bone–implant contact (BIC, 75% ± 7%) and bone volume/total volume (BV/TV, 74% ± 7%) of RAIs were significantly higher than that of conventional implants (BIC, 66% ± 5%; BV/TV, 62% ± 5%) in in vivo experiments. Further, customized abutments were designed for the RAIs, improving the masticatory ability of the beagle dogs after crown restoration. This study aims to design a personalized 2-stage RAI with compact structure and uniform roughness, in order to achieve better fracture resistance, initial osseointegration efficiency, and dispersed stress in immediate implantation. It provides a certain guiding value for standardizing the manufacture and clinical application of RAI in immediate implantation.